COMBINATION USTEKINUMAB AND VEDOLIZUMAB THERAPY FOR REFRACTORY INFLAMMATORY BOWEL DISEASE: A SINGLE INSTITUTION CASE SERIES. (22nd January 2022) - Dawoud, Nabila; Roy, Lucas; Elmoursi, Ahmed; Elkammar, Mahmoud; Eltaher, Mohamed; Barrett, Terrence; Perry, Courtney
Abstract: INTRODUCTION: Over the past 20 years, there have been great strides in the medical management of Inflammatory Bowel Disease (IBD). The advent of anti-TNF mAb therapy was transformative in the management of IBD and the positive effects are well documented 1, 2, 3 . While anti-TNF mAb biologics induce and maintain remission in IBD, a substantial portion of patients are refractory 4 . Newer biologic agents such as ustekinumab (UST) and vedolizumab (VDZ) have expanded therapeutic options for patients; however, obtaining deep remission in a subset of IBD patients remains challenging. We previously reported a successful case of deep remission in a patient with refractory stricturing Crohn's Disease (CD) treated with maximum dosage UST + VDZ therapy 5 . Since this report, we have expanded our use of this combination in refractory IBD with encouraging results. METHODS: Fifteen refractory IBD patients (12 CD, 3 UC) at the University of Kentucky were selected to initiate dual biologic therapy (DBT) with UST and VDZ. All patients previously failed other therapies, but demonstrated partial response to escalated dosing (Q4 week) of either VDZ or UST monotherapy. To determine DBT response, we analyzed fecal calprotectin (FC), C-reactive protein (CRP), albumin, BMI, hemoglobin, Harvey Bradshaw Index (HBI)/Mayo scores, endoscopic and histologic appearance. Steroid-free remission was defined by one or more of the following: 1) endoscopic and histologic remission, 2) normalization of biomarkers (FC and CRP) or 3) clinical remission defined by normalization of clinical scores AND normalization of albumin, hemoglobin, and BMI. Clinical remission was only used when endoscopic or biomarker data was not available. RESULTS: Among the 12 CD patients receiving dual biologic therapy, 11 met criteria for remission (91.6%). Six of these CD patients had complete endoscopic and histologic remission. Three CD patients did not have follow-up endoscopic or FC data, but did have normalization of albumin, CRP, hemoglobin, and HBI scores. Two CD patients were initiated on DBT for spikes in biomarkers (FC and CRP) despite clinical remission. These biomarkers normalized after initiation of DBT. One of the CD patients did not achieve response, and no one with UC (3 patients) responded. Among the successful cases, the average time to remission was 14.9 weeks. There were no adverse events or safety concerns. CONCLUSION: Dual biologic therapy with combination ustekinumab and vedolizumab is a promising and safe option for patients with refractory CD, particularly in those who demonstrate a partial response to monotherapy of either agent. This combination was not successful in our UC patients. This case series adds further support for the effectiveness of VDZ+ UST combination therapy in CD. Continued investigation is merited to support routine clinical use and improve access to this combination therapy.